Long Non-Coding RNAs: Emerging and Versatile Regulators in Host–Virus Interactions - Meng, Xing-Yu; Luo, Yuzi; Anwar, Muhammad Naveed; Sun, Yuan; Gao, Yao; Zhang, Huawei; Munir, Muhammad; Qiu, Hua-Ji (Frontiers in Immunology, 2017)
Long non-coding RNAs (lncRNAs) are a class of non-protein-coding RNA molecules, which are involved in various biological processes, including chromatin modification, cell differentiation, pre-mRNA transcription and splicing, protein translation, etc. During the last decade, increasing evidence has suggested the involvement of lncRNAs in both immune and antiviral responses as positive or negative regulators. The immunity-associated lncRNAs modulate diverse and multilayered immune checkpoints, including activation or repression of innate immune signaling components, such as interleukin (IL)-8, IL-10, retinoic acid inducible gene I, toll-like receptors 1, 3, and 8, and interferon (IFN) regulatory factor 7, transcriptional regulation of various IFN-stimulated genes, and initiation of the cell apoptosis pathways. Additionally, some virus-encoded lncRNAs facilitate viral replication through individually or synergistically inhibiting the host antiviral responses or regulating multiple steps of the virus life cycle. Moreover, some viruses are reported to hijack host-encoded lncRNAs to establish persistent infections. Based on these amazing discoveries, lncRNAs are an emerging hotspot in host–virus interactions. In this review, we summarized the current findings of the host- or virus-encoded lncRNAs and the underlying mechanisms, discussed their impacts on immune responses and viral replication, and highlighted their critical roles in host–virus interactions.